The Effect of Leverage, Institutional Ownership, and Transfer Pricing on Tax Avoidance: Profitability as a Moderating Variable (A Study on Manufacturing Companies in the Food and Beverage Sector from 2017 to 2023) - Maryanto, Maryanto; Surya, Tiara Lilis (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to: 1. Examine the effect of leverage on tax avoidance in manufacturing companies in the food and beverage sector, 2. Examine the effect of institutional ownership on tax avoidance in food and beverage companies, 3. Examine the effect of transfer pricing on tax avoidance in food and beverage companies, and 4. Test the role of profitability as a moderating variable in the relationship between institutional ownership, transfer pricing, and tax avoidance. The results of this study indicate that the analysis of leverage does not affect tax avoidance, the analysis of institutional ownership does not affect tax avoidance, and the analysis of transfer pricing does not affect tax avoidance. The profitability variable is not able to moderate the effects of leverage, institutional ownership, and transfer pricing on tax avoidance. The test reveals that profitability weakens the effect of leverage, institutional ownership, and transfer pricing on tax avoidance.